Transport Data Readiness Assessment : The Kyrgyz Republic - Vlasov, Vitaly (World Bank, Washington, DC, 2020)
The globalization of the economy is influencing not only internal and external migration and demographic processes but also urbanization in almost all countries. Big cities are growing fast, increasing the critical role of the transportation. Today, digital technologies and data analytics techniques provide tremendous opportunities to urban planners, central and municipal governments, and residents and the business sector to share and reuse data from various sources to jointly solve problems associated with transportation. The latest global trends in urban planning and management demonstrate significant increase of technology deployment, expansion of Big Data, Open Government Data (OGD), cloud computing, wide spread of mobile devices, and the internet of things. This report presents key findings of the Transport Data Readiness Assessment conducted in the Kyrgyz Republic, with special focus on urban transportation in Bishkek, the capital city. Based on the analysis of the situation, the report identifies obstacles and challenges and provides a set of recommendations to be considered by the central government and the Bishkek city administration, including relevant smart digitally enabled solutions.